Purification and Characterization of Carbonic Anhydrase from Sheep Kidney and Effects of Sulfonamides on Enzyme Activity - Demirdaǧ, R.; Çomakli, V.; Şentürk, M.; Ekinci, D.; Irfan Küfrevioǧlu, O.; Supuran, C.T. (Pergamon-Elsevier Science Ltd, 2013)
Carbonic anhydrase (CA, EC: 4.2.1.1) was purified from sheep kidney by affinity chromatography on a Sepharose 4B-tyrosine-sulfanilamide column. By means of two consecutive procedures, the enzyme (sCA) was purified 227.61-fold with a yield of 60.75%, and a specific activity of 838.89 U/mg proteins. The optimum temperature, ionic strength and pH were determined to be 35 °C, 20 mM and 8.5, respectively. The molecular weight determined by SDS-PAGE was found to be 29 kDa. The kinetic parameters, KM and Vmax values were determined for the 4-nitrophenyl acetate (p-NpA) hydrolysis reaction. Some sulfonamides were tested as inhibitors against the purified CAs enzyme. The Ki constants for benzenesulfonamide (1), sulfanilamide (2), mafenide (3), 4-(2-aminoethyl) benzenesulfonamide (4), 4-methyl-benzenesulfonamide (5), 2-bromo-benzenesulfonamide (6), naphthalene-2-sulfonamide (7), 4-amino-6-chlorobenzene-1,3-disulfonamide (8) and saccharin (9) were in the range 1.348-69.31 μM. © 2012 Elsevier Ltd. All rights reserved.
Keywords: Carbonic Anhydrase; Inhibition; Kidney Enzyme; Sheep; Sulfonamides